رقابة البرلمان على الحكومة بآلية الإستجواب - مقاربة تحليلية - ذبيح, ميلود (جامعة الوادي University of Eloued, 2012)
يعدّ الاستجواب البرلماني المدخل الطبيعي لإثارة مسؤولية الحكومة وإسقاطها ويختلف عن الآليات الاستعلامية لأنه ذو طابع أتهامي للحكومة أو لأحد أعضائها. وللاستجواب خصائص تميزه عن غيره من آليات الرقابة، ولا يتمّ توظيفه إلا بشروط وضوابط إجرائية تحت طائلة رفضه. وتختلف درجة تأثير الاستجواب على الحكومة من نظام إلى آخر، ففيما عمد المشرع الفرنسي إلى إهماله، لا زال في ألمانيا وبلجيكا والكويت الآلية الأخطر من ضمن الآليات الرقابية، وفي الجزائر لا يعدو أن يكون آلية استعلامية لجمع الحقائق، وفي كلّ الأحوال فإنّ هذه الآلية تضع بشكل أو بآخر حدودا لتعسّف الحكومات واستبدادها وتقصيرها في الأداء لمجرد التلويح به. Abstract: Parliamentary interrogation is the natural approach to raise the responsibility of the government and overthrow it, and differs from informative mechanisms because it is the nature of the charge for the government or one of its members. The interrogation of the properties that distinguish it from other control mechanisms, and are not employed only by the conditions and procedural controls under the risk of refusal. The degree of influence of the questioning on the government differs from one system to another, With the French legislator deliberately neglect, is still in Germany, Belgium, Kuwait, the mechanism of the most dangerous part of regulatory mechanisms, and in Algeria is merely a mechanism for the collection of informative facts, In all cases, the mechanism is put in one form or another are limits to the arbitrariness of authoritarian governments, and its failure in the performance of just waving it.
Keywords: الرقابة؛ الاستجواب؛ الحكومة؛ البرلمان؛ مسؤولية الحكومة؛ طابع اتهامي؛ ملتمس الرقابة